The Influence of Celebrity Endorser, Country of Origin, and Shopping Lifestyle on Purchase Decision for Somethinc Products - Adriana, Erica; Hellyani, Catharina Aprilia; Beatriz, Beatriz (East Asian Journal of Multidisciplinary Research, 2024)
This study’s goal is to analyze and determine the effect of celebrity endorser, country of origin, and shopping lifestyle on purchase decisions for Somethinc products. This study uses quantitative methods with explanatory research. The population in this study used is Indonesians who have used Somethinc products with a sampling of 272 respondents. The sampling procedure used is non-probability with purposive sampling technique. The data analysis technique used in this study is multiple linear regression. The results of this study shows that celebrity endorser, country of origin, and shopping lifestyle both partially and simultaneously have a positive influence on purchase decisions for Somethinc products. The combination of choosing the right celebrity endorser, emphasizing Indonesia's reputation as the country of origin, and a deep understanding of consumers' shopping lifestyle will strengthen Somethinc's overall marketing strategy. The implementation of this strategy can help the company increase sales, build loyalty, and expand market share in the competitive beauty industry.